2020
DOI: 10.3390/biom10121702
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in NAFLD: Role of Nutrients and Food Contaminants

Abstract: Non-alcoholic fatty liver disease (NAFLD) is often the hepatic expression of metabolic syndrome and its comorbidities that comprise, among others, obesity and insulin-resistance. NAFLD involves a large spectrum of clinical conditions. These range from steatosis, a benign liver disorder characterized by the accumulation of fat in hepatocytes, to non-alcoholic steatohepatitis (NASH), which is characterized by inflammation, hepatocyte damage, and liver fibrosis. NASH can further progress to cirrhosis and hepatoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 436 publications
(595 reference statements)
1
59
0
3
Order By: Relevance
“…In this regard, clinical evidences have demonstrated the beneficial action of antioxidants in lipid metabolism dysfunction such as MAFLD. Both classical antioxidants (vitamins C and E) and other natural dietary antioxidants such as coffee components or flavonoids (hesperetin and derivates) have been described as potential therapies in MAFLD [ 54 , 55 ]. MAFLD patients have high levels of ROS and lipid peroxidation products, as well as decreased activity of the main antioxidant enzymes, compared to healthy subjects [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, clinical evidences have demonstrated the beneficial action of antioxidants in lipid metabolism dysfunction such as MAFLD. Both classical antioxidants (vitamins C and E) and other natural dietary antioxidants such as coffee components or flavonoids (hesperetin and derivates) have been described as potential therapies in MAFLD [ 54 , 55 ]. MAFLD patients have high levels of ROS and lipid peroxidation products, as well as decreased activity of the main antioxidant enzymes, compared to healthy subjects [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective type of longterm treatment of NAFLD remains lifestyle modification (4,5). Although the pathogenesis of NAFLD is not well-understood, the leading hypothesis is the hepatic fat accumulation owing to insulin resistance followed by oxidative stress arising from reactive oxygen species produced primarily by mitochondria (6,7). The liver plays a critical role in the metabolism of vitamins, and deregulation of vitamins metabolism may contribute to the initiation and progression of NAFLD (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts must be made to reduce the burden of NAFLD.NAFLD is characterized by abnormal lipid accumulation in hepatocytes (Boutari et al, 2018). Studies have revealed that being overweight, oxidative stress, and insulin resistance are the main causes of NAFLD (Gomaraschi et al, 2019;Rives et al, 2020). NAFLD can progressively develop into cirrhosis and subsequently into hepatocellular carcinoma.…”
mentioning
confidence: 99%